2021
DOI: 10.3390/polym13244446
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics, Isotherm and Thermodynamic Studies for Efficient Adsorption of Congo Red Dye from Aqueous Solution onto Novel Cyanoguanidine-Modified Chitosan Adsorbent

Abstract: Novel Cyanoguanidine-modified chitosan (CCs) adsorbent was successfully prepared via a four-step procedure; first by protection of the amino groups of chitosan, second by insertion of epoxide rings, third by opening the latter with cyanoguanidine, and fourth by restoring the amino groups through elimination of the protection. Its structure and morphology were checked using Fourier-transform infrared spectroscopy (FTIR), X-ray diffraction (XRD) and scanning electron microscopy (SEM) techniques. The adsorption c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(30 citation statements)
references
References 49 publications
0
23
0
Order By: Relevance
“…Therefore, electrostatic attraction between the positively charged surface of PA-12/PC nanocomposite (pH < 5) and negatively charged CR results in adsorption, while from pH 5 to 10, there is electrostatic repulsion between anionic charges of both PA-12/PC nanocomposite and CR, resulting in decreased adsorption. Recent studies have also reported pH 4 as an optimum pH for CR adsorption 69 , 70 . For other cationic dyes, i.e., BG, MB, and MR, qe increases with increasing pH from 2 to 6 and then decreases slightly with increasing pH from 8 to 10.…”
Section: Resultsmentioning
confidence: 98%
“…Therefore, electrostatic attraction between the positively charged surface of PA-12/PC nanocomposite (pH < 5) and negatively charged CR results in adsorption, while from pH 5 to 10, there is electrostatic repulsion between anionic charges of both PA-12/PC nanocomposite and CR, resulting in decreased adsorption. Recent studies have also reported pH 4 as an optimum pH for CR adsorption 69 , 70 . For other cationic dyes, i.e., BG, MB, and MR, qe increases with increasing pH from 2 to 6 and then decreases slightly with increasing pH from 8 to 10.…”
Section: Resultsmentioning
confidence: 98%
“…If the value of activation energy requirement is small (E a = 0–40 kJ·mol −1 ), and since the forces involved are weak, the adsorption process flows by chemical ion exchange. If the activation energy E a < 40 kJ·mol −1 , then the adsorption process is physical in nature, whereas if the E a value is within the range of 40–800 kJ·mol −1 , then the adsorption process is chemisorption in nature and involves forces much stronger (chemical bonds) than physical adsorption [ 46 , 47 , 48 , 49 , 50 ]. Therefore, the values of activation energy ( E a ) (i.e., minimum energy required for a reaction to occur), calculated using the Arrhenius equation (E a = 7.126 and 11.124 kJ·mol −1 ), are less than 40 kJ·mol −1 for KS44-0 and KS44-20, respectively ( Table 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…The Langmuir isotherm is the simplest and most common model to describe adsorption and can be effective when describing chemical adsorption. The adsorption in this model is assumed to be a monolayer, where a single layer of molecules is adsorbed on the adsorbent surface [14]. Therefore, the adsorbent surface is homogeneously structured, wherein all adsorption sites are identical, energetically equivalent, and uniform.…”
Section: Enzyme Immobilizationmentioning
confidence: 99%